Incidental L2 lexical acquisition in reading: the role of L2-gloss frequency and learner proficiency. Issue 5 (20th October 2019) - Zhao, Ting; Ren, Juan
ABSTRACT: The present study aims to investigate the effects of gloss use, L2-gloss frequency and learner proficiency on incidental L2 lexical acquisition. A total of 163 university students in China were assigned to one of the three reading conditions: no gloss (NG), higher frequency L2 gloss (HFLG) and lower frequency L2 gloss (LFLG). The participants read a text for the purpose of comprehension, and then completed immediate and delayed post-tests for recall and recognition. We then surveyed the participants' views on gloss use and L2-gloss types. The results showed that the glossed groups significantly outperformed the NG group in immediate recall and recognition. The gloss advantage, however, was absent in delayed recall but retained in delayed recognition. The gloss-frequency effect was not observed with higher proficiency participants, but among lower proficiency participants, HFLG was superior to LFLG on immediate recall. The questionnaire results revealed that learners favoured HFLG for the ease of encoding and comprehending. Based on these findings, pedagogical implications are advanced for supporting incidental L2 lexical acquisition within formal educational contexts.